Radical Formation in X-Irradiated Amino Acids and Its Relation to The Crystal Structures - Frida U. Ermawati (Indonesian Journal of Physics, 2003)
Electron spin resonance (ESR) spectra from L and DL optical isomers of six amino acids have been observed after x-irradiation at 77K. A Varian E-12 spectrometer equipped with a rectangular parallelepiped microwave cavity to produce TE102 mode was utilized for this purpose. It was obtained that for most of the acids, spectra from the L and DL isomers are different at corresponding temperature in the range from 77 to 300K. These differences are attributed to differences in crystal structure, especially to the conformation of the amino group with respect to the adjacent carboxyl group of a system.